2021
DOI: 10.1007/s00508-021-01910-2
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI study of cognitive remediation in drug-naïve subjects diagnosed with first episode schizophrenia

Abstract: Summary Objective The purpose of our functional magnetic resonance imaging (fMRI) study was to examine brain activity using a “1-back” paradigm as working memory task in drug-naïve subjects with first episode schizophrenia before and after cognitive remediation training. Methods In this study 15 drug-naïve first episode subjects who met DSM-IV criteria for schizophrenia were randomized to receive either atypical antipsychotics (AP, n = 8) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Cognitive remediation and related psychosocial interventions have also been associated with increases in functional connectivity in frontal cortex 272 and increased frontal activation during task‐based fMRI 273‐275 . Activation in areas other than the frontal cortex have also been observed, including the anterior cingulate and parietal cortex 275,276 . Recent reviews investigating cognitive remediation in individuals with schizophrenia revealed positive associations between cognitive improvements and functional and structural changes in frontal brain regions 277,278 .…”
Section: Fmri In Relation To Treatment: Response/resistance Mechanism...mentioning
confidence: 99%
“…Cognitive remediation and related psychosocial interventions have also been associated with increases in functional connectivity in frontal cortex 272 and increased frontal activation during task‐based fMRI 273‐275 . Activation in areas other than the frontal cortex have also been observed, including the anterior cingulate and parietal cortex 275,276 . Recent reviews investigating cognitive remediation in individuals with schizophrenia revealed positive associations between cognitive improvements and functional and structural changes in frontal brain regions 277,278 .…”
Section: Fmri In Relation To Treatment: Response/resistance Mechanism...mentioning
confidence: 99%
“…Cognitive impairment is a key feature of patients with schizophrenia, involving deficits in attention, information processing, executive function, language and in memory, especially in verbal learning ( Green and Harvey, 2014 ). Cognitive dysfunction can already manifest itself during the initial manifestation of schizophrenia ( Furtner et al, 2021 ); it often persists in the course even after acute symptoms have subsided ( Green et al, 2004 ) and can influence the functional outcome in schizophrenia as well as in affective disorders ( Sachs et al, 2020 ). Despite such findings, screening for cognitive deficits frequently still is insufficient in routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%